Greenhouse and field evaluations of commonly occurring weed species for their host suitability to Meloidogyne species. Issue 1 (2nd January 2016) - Ntidi, K.N.; Fourie, H.; Daneel, M.
Abstract : Since weeds serve as hosts for nematode pests, the host status of 20 weed species (commonly occurring in fields of developing farmers) to Meloidogyne incognita and M. javanica, respectively, were investigated. Greenhouse studies showed that seven weed species had Rf values >1 for both nematode species indicating susceptibility, while 13 had Rf values ≤ 1 indicating resistance. Greenhouse results showed that Hibiscus trionum and Amaranthus tricolor were identified as the most susceptible and Chenopodium carinatum and Datura ferox the poorest hosts for M. incognita and M. javanica . For field experiments at Kuruman, Solanum retroflexum was the most susceptible weed to a M. javanica population, while the same was evident for H. trionum at Nelspruit, where a mixed population of M. incognita and M. javanica occurred and at Potchefstroom, where a population of M. incognita was present. Results from this study indicated that certain weed species are highly susceptible to root-knot nematodes and should be removed timely and effectively to prevent population level increases of root-knot nematode pests in the fields of farmers.